Pengaruh Tingkat Pengungkapan Corporate Social Responsibility Terhadap Asimetri Informasi Pada Perusahaan Sektor Pertambangan dan Barang Konsumsi Di Indonesia dengan Variabel Kontrol Firm Size dan Analyst Following - Crystalita Crystalita Crystalita; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
The affect of corporate social responsibility (CSR) on financial performance had been studied before. However, there were only a few studies about the effect of CSR on information asymmetry. The aim of this research was to examine the affect of CSR disclosure level towards information asymmetry, which measured by bid-ask spread in mining and consumption industries firm listed in Indonesia Stock Exchange (IDX). The CSR disclosure level was measured by using GRI Index 3.1, whereas information asymmetry was measured by using bid-ask spread. There were two control variables used in this research: firm size and analyst following. This study was conducted on mining and consumption industries firms in Indonesia in the period of 2008 to 2015 with a total sample of 191 firm years. The results of this research indicated that corporate social responsibility disclosure level had negative affect on information asymmetry. The control variables of firm size and analyst following also had negative affect on information asymmetry.